Developing Learning Materials in Addition and Subtraction of Fractions with Realistic Mathematics Approach for Students Grade 4 - Ari Wijayanti (Southeast Asian Mathematics Education Journal, 2017)
This study aims to describe the development process of learning materials that consists of lesson plan, student activity sheet, and fraction card. The study focuses on teaching addition and subtraction of fractions through realistic mathematics education. The development process used the Four-D model which consists of four steps: define, design, develop, and disseminate. In the first step (define), the teacher established the terms of learning by determining fundamental problem, analyzing students, and specifying instructional objectives. In the second step (design), the prototype of learning materials was constructed as a test standard, choosing the proper media and selecting the format. On the third step (develop), the learning materials were validated by the experts and then revised. Once the learning materials were ready they were tested in classroom. The teacher then collected data to measure the quality of the learning materials. The last step, dissemination, was the implementation of learning materials on a broad scale. From this step, the teacher collected data to measure the effectiveness of the learning. This study generated good learningmaterials and supported students Grade 4 to learn about addition and subtraction of fractions. While the results are providing some promising directions, a much larger study would be needed to determine if the results are due to the approach or due to the teachers’ enthusiasm or what is known as the Hawthorne Effect.